2014
DOI: 10.11648/j.avs.20140206.12
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Plasmid in Listeria monocytogenes Isolated from Fresh Raw Milk in Nigeria

Abstract: Abstract:Aims: To determine the presence of plasmids in Listeria monocytogenes strains isolated from fresh raw milk from healthy cattle in Nigeria and also determine its role in antibiotics resistance since this organism is a food borne pathogen of public health importance. Methods and results: Isolation of Listeria monocytogenes was done using selective enrichment and isolation protocol, as recommended by United States Department of Agriculture (USDA) and Association of Analytical Chemists/ International Dair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a study in Northern Ireland, reported in 2001, only two sporadic isolates of 45 tested showed resistance to tetracyclines when tested for resistance to ampicillin, gentamicin, streptomycin, sulphonamides, erythromycin, chloramphenicol, cephalothin and tetracyclines (Harvey and Gilmour, 2001). In non-EU countries, resistance to tetracycline and penicillin has been reported in isolates in Malaysia in 2012 (Jamali et al, 2013) and multiple resistance has recently been reported in Listeria isolates from raw milk in Nigeria (Uwanibe et al, 2014).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
“…In a study in Northern Ireland, reported in 2001, only two sporadic isolates of 45 tested showed resistance to tetracyclines when tested for resistance to ampicillin, gentamicin, streptomycin, sulphonamides, erythromycin, chloramphenicol, cephalothin and tetracyclines (Harvey and Gilmour, 2001). In non-EU countries, resistance to tetracycline and penicillin has been reported in isolates in Malaysia in 2012 (Jamali et al, 2013) and multiple resistance has recently been reported in Listeria isolates from raw milk in Nigeria (Uwanibe et al, 2014).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%